Dispersal and habitat preference of juvenile emperor penguins—implications for conservation management - Makhado, Azwianewi Benedict; Crawford, Robert J. M.; Dyer, Bruce M.; Masotla, Makhudu; Lowther, Andrew (Royal Society Open Science, 2025)
Seabirds can disperse widely when searching for prey, particularly during nonbreeding periods. Conservation measures predominately focus on protecting breeding colonies, while spatial protection at sea is often based on knowledge of the distribution of breeding adults, despite accumulating evidence that marine habitats used by immature birds sometimes differ from those of adults. Juvenile emperor penguins from Atka Bay, west Dronning Maud Land, Antarctica, tracked immediately after fledging performed long migrations to the northern extents of the Convention for the Conservation of Antarctic Marine Living Resources subareas 48.4 and 48.6. Individuals did not remain long at their northern positions, before commencing a rapid southerly movement to within a few hundred km of the marginal ice zone (MIZ). The initial migratory movement was broadly synchronous across individuals. The southward movement and subsequent change to area-restricted searching were consistent with the MIZ representing a potentially important feeding habitat for juvenile emperor penguins. Spatio-temporal management mechanisms may be beneficial in reducing threats to these young penguins.
Keywords: Dronning Maud Land; biologi; marine økosystemer; ornitologi; pingviner; sjøfugler; telemetri; økologi

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Investigating Climate Change by Digital Analysis of Blue Ice Extent on Satellite Images of Antarctica - Orheim, Olav; Lucchitta, Baerbel (Annals of Glaciology, 1990)
Keywords: Dronning Maud Land; glasiologi; klimaendringer; satellitt; telemetri